Legal Studies of Marriage Registration and the Problems of Isbat Nikah Polyandry and Its Legal Consequences for Children - Haeratun, Haeratun (Formosa Journal of Multidisciplinary Research, 2024)
One of the important issues in marriage law in Indonesia is the registration of marriages and divorces in the Religious Courts. This happens because some of the rules in these regulations are considered relatively new because they have not been mentioned in the classical jurisprudence books which are used by the Indonesian people, especially the ulama. In statutory regulations as contained in Article 2 paragraph (2) of Law Number 1 of 1974 concerning Marriage jo. Article 5 of the Compilation of Islamic Law states that every marriage must be recorded. This research discusses; What is the form of registration of polyandrous marriages and what are the problems with the legal status of polyandrous marriages and the legal consequences for children. This type of research is doctrinal research or normative legal research. Meanwhile, the approach used is a statutory approach, a conceptual approach and a comparative approach and the legal analysis uses descriptive qualitative analysis, namely by formulating and explaining significantly several legal issues that are the object of study in this research.